Physical layer jamming attack using waypoint mobility model in WLAN / Ahmad Yusri Dak, Nurul Fazliana Samsudin and Noor Elaiza Abdul Khalid - Yusri Dak, Ahmad; Samsudin, Nurul Fazliana; Abdul Khalid, Noor Elaiza (UiTM Cawangan Perlis, 2018)
Sharing nature of wireless medium provides various challenging features among various group of users. This is one of various services offered by Wireless Local Area Network (WLAN). Thus, due to popularity of WLANs, user experience suffers from various security threats especially jamming based Denial-of-Service (DoS) attack. The attacks are focused on radio channels where the transmission channel interfere with jamming attacks by sending high frequency signal to disturb the communication between the users in network. Most of attack exists at physical layer are detected randomly movable and less static attack are found. Therefore, the objective of this research is to study the pattern of randomly movable node and performance of physical layer jamming attack using Waypoint Mobility Model. To address these evaluation, a simulation model consists of physical layer jamming attack will be developed using OPNET. The performance involved physical layer attack that are evaluated using three performance metrics which is Bit Error Rate (BER), Signal-to-Noise Ratio (SNR), and throughput. Outcome concluded that these threeperformance metrics show as a significant impact as detection mechanism and offer a future comprehensive research based on DoS attack.